Impact of handoff protection strategies on cellular mobile system capacity. - Yi Xu
In the future cellular mobile systems, the steadily growing mobile subscriber community and their demand for diversity of service place great challenge on the bandwidth utilization, especially in the wireless network part, as radio spectrum is a limited resource. Carefully planned radio usage is critical for both system capacity and service quality. Current research work in literature cares about two aspects of the service provision capability of cellular networks. One is capacity related that emphasizes the user admission capability and the other is service quality related that targets the connection continuity. However, actually achievable user accommodation capability is a cooperative result of both aspects. This paper mathematically reveals the impact of handoff protection, which is introduced to enhance connection robustness, on the capacity of cellular mobile systems. We first extract the basic mobility characteristics from the real world cellular environment to establish an ideal traffic model. Then a Markov approach is proposed to analyze the correlation between the user admission capability and the channel reservation, which is one strategy for handoff protection, and furthermore to answer the question how the user accommodation capability is affected by channel reservation in this ideal model. Simulation outcomes are provided for the creditability verification on the theoretical results. We find that system capacity and service quality are two conflicting objectives and tradeoff is inevitable. Finally, a dynamic channel reservation scheme is described to provide a mechanism for the tradeoff coordination between system revenue and service quality.
Keywords: 3G mobile communication; Markov approach; Bandwidth utilization; Cellular mobile system capacity; Channel reservation method; Connection continuity; Handoff protection strategy; Mobile subscriber community; Personal communication system; Service diversity; Service quality; Traffic model; User accommodation capability; User admission capability